Reconstructing Sunan Ampel’s “Moh Limo” Philosophy as an Islamic Digital Ethics Framework for Character Education in the Era of Artificial Intelligence - Muhammad Syukri Azizi; Abdul Rosyid Teguhdin Hamid (Golden Ratio of Data in Summary, 2026)
The rapid development of artificial intelligence (AI) presents both opportunities and ethical challenges for character education. Issues such as AI-assisted plagiarism, misinformation, privacy violations, online gambling, and moral degradation indicate that digital literacy requires an ethical foundation rooted in Islamic values. This study reconstructs Sunan Ampel’s Moh Limo philosophy as an Islamic digital ethics framework for strengthening character education in the age of AI. It employs library research and a conceptual approach. Data were drawn from scholarly literature on Moh Limo, digital ethics, character education, digital literacy, and AI and analyzed through thematic analysis and conceptual synthesis. The findings demonstrate that the five Moh Limo values—moh main, moh maling, moh madon, moh ngombe, and moh madat—remain relevant as a foundation for digital ethics. These values are reconstructed as principles of self-control, honesty, responsibility, preservation of dignity, critical thinking through tabayun, and prudent use of technology. This study contributes a locally grounded Islamic digital ethics framework that strengthens character education and may provide a conceptual basis for policy development, teaching and learning, and future research in the age of AI.